Effects of probiotic on gut microbiota in children with acute diarrhea: a pilot study - Dion Darius Samsudin; Agus Firmansyah; Eka Laksmi Hidayati; Irene Yuniar; Mulya Rahma Karyanti; Rosalina Dewi Roeslani (Indonesian Pediatric Society, 2020)
Background Acute diarrhea is a common health problem in Indonesia. During acute diarrhea, changes in gut microbiota are marked by decrease beneficial microbes Bifidobacterium and Lactobacillus, and increased pathogenic bacteria Enterobacter and Clostridium. Such microbial imbalances are known as dysbiosis. Treatment with probiotics may help repair dysbiosis, quicken healing time, and decrease complications. Objective To assess for dysbiosis during acute diarrhea, and determine if it can be normalized by probiotic treatment. Methods This placebo-controlled, unblinded clinical trial was performed in Budhi Asih District Hospital, Jakarta, from January to March 2018. Twenty-four children age 6-24 months with acute diarrhea and 12 healthy children were enrolled. First fecal specimen was collected for all subjects and analyzed using non-culture real time PCR to count the population of Lactobacillus, Bifidobacterium, Enterobacter, Clostridium, and all bacteria. Children with diarrhea were assigned to probiotic or placebo treatment for 5 days and the second fecal specimen was analyzed two weeks after the diarrhea subsided. Results Prior to treatment, significant higher amounts of Lactobacillus were observed in children with acute diarrhea than in healthy controls [median (interquartile range/IR): 1.52x103 (1.22x104) vs. 6.87x10 (2.41x102), respectively; proportion in percentage (from total bacteria population): 0.044% vs. 0.003%, respectively]. However, median (IR) Clostridium was significantly higher in healthy controls than in children with acute diarrhea [2.37x102 (4.64x103) vs. 4.67 (1.50x102), respectively (P<0.05), with proportion of 0.01% vs. 0.0001%, respectively]. Children who received probiotics had significantly higher count of Bifidobacterium compared to the placebo group [1.94x104 (4.97x104) vs. 1.74x103 (2.08x107), respectively, with proportion of 0.394% vs. 0.081%, respectively]. Conclusion This pilot study do not find evidence of dysbiosis in children with acute diarrhea. Group who received probiotic had higher Bifidobacterium count compared towards those who received placebo.